Multi-scale process studies in the tropics: results from lightning observations - Petersen, Walter A., author (Colorado State University. Libraries, 1997)
Cloud-to-ground (CG) lightning and meteorological observations collected in the tropics were analyzed to address the following question: What do observations of lightning tell us about processes occurring over multiple scales in the tropical atmosphere? An emphasis was placed on the analysis of observations collected over the western Pacific warm-pool during TOGA COARE. Large-scale observations from COARE suggest that the occurrence of lightning over the western Pacific Ocean is a sensitive function of both the magnitude and vertical distribution of convective available potential energy (CAPE). Small variations in the marine boundary layer humidity were highly correlated to variations in the CAPE and/or boundary-layer 8w. In tum, small increases (O[0.5° C]) in the boundary-layer 8w, were associated with disproportionate increases in lightning activity. The diurnal cycle of CG lightning exhibited a pronounced maximum (minimum) around 2 a.m. (12 p.m.) local-time. Diurnal cycles of CAPE, convective and total precipitation exhibited similar diurnal cycles, but were weaker in amplitude. Over cloud-scales, upward-building 30 dBZ reflectivity cores extended to elevations colder than -10°C in lightning-producing tropical oceanic convection. Additionally, mean updraft strengths (when observed) in several Lightning-producing cases exceeded 6 m s-1 near the -10°C level. These observations support the hypothesis that updraft magnitudes between the 0°C and -10°C levels in tropical convection must exceed the terminal fall-speed of millimeter sized liquid and frozen drops in order to provide the requisite hydrometeor mass to electrification processes in the cold regions of the cloud. To investigate the coupling between cloud-scale electrification, kinematics, microphysics, and the large-scale thermodynamic environment, a one-dimensional cloud-model with a fourclass bulk-microphysical ice scheme and a parameterization for non-inductive charging processes, was used to simulate tropical convection. In the cloud-simulations, convective heating profiles associated with lightning (non-lightning) producing convection were associated with a more pronounced upper-level (low-level) heating peak and an increased (decreased) contribution by ice-processes to the total surface rainfall. Since the rainfall process and lightning production become increasingly more correlated as contributions from the ice-phase to the total rainfall increase, we investigated the correlation between rainfall and lightning over large spatial and temporal scales for many different rainfall regimes. The results indicate that CG lightning flash density and rainfall are well correlated in warm-season rainfall regimes where highly electrified convection is prolific. In certain situations, it may be possible to use CG-lightning flash density to diagnose warm-season monthly rainfall totals, or differentiate between rainfall regimes.
March 1997.
Also issued as author's dissertation (Ph.D.) -- Colorado State University, 1997.
Keywords: Lightning -- Tropics; Convective clouds -- Tropics